Effects of riverine nutrient enrichment and sediment reduction on high primary productivity zone in the Yangtze River estuary: historical reconstruction and future perspective - Yan Song; Maotian Li; Xiaoqiang Liu; Weihua Li; Huikun Yao; Yan Liu; Jing Chen (Frontiers in Marine Science, 2025)
The high primary productivity zone (HPPZ) of estuaries is known for its flourishing fisheries and active interactions with coastal and oceanic ecosystems. However, the spatiotemporal patterns and underlying mechanisms that regulate the HPPZ remain unclear, especially in the face of drastic changes in riverine inputs. Using 40 years of in situ monitoring data along the Yangtze River estuary, the spatiotemporal evolution of the HPPZ regulated by basin-estuarine-offshore flux fluctuations has been reconstructed for the past and conclusions drawn for future developments. Moreover, the biological processes that influence the formation of the HPPZ were explored within the context of estuarine filtration and buffering effects. The obtained dataset includes chlorophyll a (Chl-a) concentrations and multiple environmental factors. The results displayed that the HPPZ is characterized by a high annual average Chl-a concentration of 3.6 ± 2.4 μg/L, which is driven by sufficient light and nutrient availability that promote phytoplankton blooms. In contrast, the inner high turbidity zone exhibits an average annual Chl-a concentration of 1.0 ± 0.7 μg/L, primarily due to limited light availability inhibiting phytoplankton growth. Meanwhile, the outer lower nutrient zone, with an average annual Chl-a concentration of 0.9 ± 1.1 μg/L, results from nutrient deficiencies that limit phytoplankton growth. Notably, the synergistic effect of sediment declines and eutrophication has resulted in a 6.5 μg/L increment of the HPPZ’s annual Chl-a concentration and a 3628 km² expansion of its area extent over 40 years. This significant change is attributed to the increase in water transparency resulting from a reduction in sediment transported from the watershed to the sea, along with an increase in riverine nitrogen and phosphorus discharge. A future projection, based on the historical total suspended matter and nutrients over the past 40 years, suggests that annual Chl-a concentration in the HPPZ will reach 10.5 μg/L, and the area is projected to increase to 7,904 km² by 2050. This study presents the first quantification of Chl-a concentrations and spatial range of the HPPZ in the estuary, focusing on the interaction between riverine and oceanic materials. These findings offer a deeper understanding of managing ecological risks in large estuaries.